2017
DOI: 10.7205/milmed-d-16-00407
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Tactical Safety of Endotracheal Intubation Under Darkness

Abstract: Considering this finding, we still strongly recommend that it would be relatively safer to open the ML blade inside the mouth and to perform the procedures under a PL. In chaotic environments where it might become necessary to provide civilian health services for humanitarian aid purposes (Red Crescent, Red Cross, etc.) without NVGs, we believe that it would be relatively safer to open the CL blade inside the mouth and to perform the procedures under a PL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The use of a light source during medical interventions will reveal the location of the casualty and friendly units, making them an open target for enemy units in unknown locations and equipped with observation equipment 4. In this regard, the use of a visible light source has known tactical disadvantages that may result in becoming a target for enemy 2 4. The use of NVGs provides tactical advantages and security during incursions or retreats, preventing units from being spotted by enemy units.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of a light source during medical interventions will reveal the location of the casualty and friendly units, making them an open target for enemy units in unknown locations and equipped with observation equipment 4. In this regard, the use of a visible light source has known tactical disadvantages that may result in becoming a target for enemy 2 4. The use of NVGs provides tactical advantages and security during incursions or retreats, preventing units from being spotted by enemy units.…”
Section: Discussionmentioning
confidence: 99%
“…Although the tactical use of NVGs has been included in the routine training programme of combatant units, their use has not become widespread in the training and practice of CMS 3 7 8. It has been recommended that the use of NVGs must be included in practical and theoretical training in medical/tactical scenarios in dark conditions 3 4 7 9. It has also been reported that increasing user experience through practical training increases success rates in interventions using NVGs under dark conditions 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation